Dominio técnico de la Naturaleza: olvido y cosificación (2021)
From the reflections of Theodor W. Adorno and Max Horkheimer, this article explores the critique of the technical domination of nature based on instrumentalreason as a form of alienation and forgetfulness, the product of a “second nature” that alienates people from their relationship with nature. Uncovering the decisive issue of forgetting nature as a product of the reification of the subject should provide reflective arguments for a better understanding of our current relationship with nature and with ourselves